2019
DOI: 10.18621/eurj.447027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cardiac rehabilitation on neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio in ST elevation myocardial infarction patients

Abstract: Objectives: Cardiac rehabilitation is known to have positive effects on the inflammatory processes. The neutrophil-to-lymphocyte ratio (NLR) and the platelet-to-lymphocyte ratio (PLR) were found to be indicative of inflammation. The purpose of this study is to determine the effects of cardiac rehabilitation on the NLR and PLR ratios of ST elevation myocardial infarction (STEMI) patients. Methods: The study includes 101 STEMI patients that underwent primary percutaneous coronary intervention (PCI). The patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…A recent study found that after a 30-session rehabilitation program among cardiac patients, CRP level, neutrophil count, platelet count, and the ratio of NLR and PLR decreased significantly; however, the change in lymphocyte count was not statistically significant [12]. Another recent study found that the levels of leukocytes, neutrophils, NLR, and PLR diminished significantly after 8 weeks of rehabilitation among STEMI patients (ST-segment elevation MI) in the CR group [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study found that after a 30-session rehabilitation program among cardiac patients, CRP level, neutrophil count, platelet count, and the ratio of NLR and PLR decreased significantly; however, the change in lymphocyte count was not statistically significant [12]. Another recent study found that the levels of leukocytes, neutrophils, NLR, and PLR diminished significantly after 8 weeks of rehabilitation among STEMI patients (ST-segment elevation MI) in the CR group [10].…”
Section: Discussionmentioning
confidence: 99%
“…After rehabilitation was applied to the CR group, the difference between the two groups was NS anymore. They reported that NLR and PLR parameters significantly decreased after 30 sessions of CR in the CR group, while it was not the case with the control group [10]. Another study revealed that a 6-week CR program brought about a significant reduction in hs-CRP levels among acute coronary syndrome patients [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are also related to the non-dipper status of the hypertensive patients, resulting in more cardiovascular complications [4,[6][7][8][9]17]. In a recent study, Fest et al [18] followed up 8715 individuals for 12 years (2002-2014) to assess NLR association with mortality in the general population and concluded that NLR is a strong and independent risk factor for mortality in elderly population.…”
Section: Discussionmentioning
confidence: 99%